Double-Stranded RNA as an Inhibitor of Protein Synthesis and as a Substrate for a Nuclease in Extracts of Krebs II Ascites Cells - Robertson, Hugh D. (1973)
Concentrations of double-stranded RNA above about 0.1 μg/ml inhibit translation of encephalo-myocarditis viral RNA and mouse globin messenger RNA in extracts of Krebs II ascites cells. Protein synthesis initially proceeds at the control rate, then abruptly shuts off in a manner similar to that observed in reticulocyte lysates [Hunt, T. & Ehrenfeld, E. (1971) Nature New Biol. 230, 91-94]. Substantially higher concentrations of double-stranded RNA are required to give this effect in ascites extracts. Subcellular fractions of Krebs II ascites cells contain a nucleolytic activity capable of digesting several natural and synthetic double-stranded RNAs. This nuclease is most active under conditions of protein synthesis, and part of the activity remains associated with ribosomes upon sedimentation. It is probably because of digestion of double-stranded RNA by this nuclease that higher concentrations of double-stranded RNA are required for inhibition of protein synthesis in Krebs cell extracts than in reticulocyte lysates.